Modelling of PID-Fuzzy Controller for Speed Control of Brushless DC Motor to Improve Steady State Performances - Pokharel, Bigyan; Pandey, Bimal; K.C., Ajay; Gouli, Sangam; Dhami, Sandeep (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.